If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = 8x + 14 Reorder the terms: -7 + x = 8x + 14 Reorder the terms: -7 + x = 14 + 8x Solving -7 + x = 14 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -7 + x + -8x = 14 + 8x + -8x Combine like terms: x + -8x = -7x -7 + -7x = 14 + 8x + -8x Combine like terms: 8x + -8x = 0 -7 + -7x = 14 + 0 -7 + -7x = 14 Add '7' to each side of the equation. -7 + 7 + -7x = 14 + 7 Combine like terms: -7 + 7 = 0 0 + -7x = 14 + 7 -7x = 14 + 7 Combine like terms: 14 + 7 = 21 -7x = 21 Divide each side by '-7'. x = -3 Simplifying x = -3
| log(9)*3-x=log(9)*5x-15 | | -8x+1=-80 | | 2s+4h+6u+8t=100 | | 2s+3h+5u+6t=100 | | X-.2X=81 | | -8+4x=-28 | | 21-5x=13-7x | | 52+x-28=55 | | x^2-24x=44 | | log(4)4x-20=5 | | 2+2=.5x-1 | | 75+x-60=40 | | 2+2=2x-1 | | 2+2=22x-1 | | 64+x-39=47 | | 28+x-20=42 | | 1.25-22= | | 9+10=x+1 | | 45+x-5=80 | | 9h-27=63 | | T=7M+3 | | x^2(x-3)-2x(x-3)+(x-3)=0 | | 100x+y=x+50y | | 100x+y=x+2y | | 10x+y=x+2y | | 347*25=8675 | | 4x(5x+6)=2(2x-2) | | -2(y+3)+3(2y-1)=7+y | | 7=-(4n+5) | | (1-u)(5u-3)=0 | | 144=[(2x-17)+9]9 | | ln(2-2x)=1 |